NEW RECORDS OF CAPILLARIIDAE SPECIES (NEMATODA, ENOPLIDA) PARASITING BATS (MAMMALIA, CHIROPTERA) IN BRAZIL - Munhoz de Mello, Érica (2019)
During a helminthological survey on bats from Minas Gerais state, Brazil, we found 3.13% of bats parasitized with capillarids. Aonchotheca pulchra (Freitas, 1934), Tenoranema rivarolai (Lent et al., 1946), and some specimens of capillarids non-identified were registered. This is the first report of A. pulchra in Minas Gerais state and the second report of T. rivarolai in South America.